Religious Tolerance In Indonesian Language Learning In MI: Exploration Of Diversity Values And Practical Implementation - Oktaviani, Atiko Nur; Suharto, Abdul Wachid Bambang (Moderatio: Jurnal Moderasi Beragama, 2024)
Indonesia, as a country rich in cultural, religious, and ethnic diversity, faces challenges in maintaining harmony and tolerance in its society. The importance of tolerance education from an early age, especially at Madrasah Ibtidaiyah (MI), is a primary focus. Indonesian language learning at MI plays a strategic role in teaching students the values of diversity and religious tolerance. Recent data shows significant challenges in fostering tolerant attitudes, particularly among the younger generation. Learning Indonesian at MI aims not only to improve students' language skills but also to introduce them to the concepts of tolerance and respect for differences. Integrating values of diversity into the curriculum allows students to appreciate differences and understand diverse perspectives in society. Consequently, the young generation emerging from MI is more open, accepting, and capable of maintaining harmony amidst Indonesia's diversity. Thus, learning Indonesian at MI is not only a means of communication but also a stage for character formation rooted in the values of diversity, which are essential to the Indonesian national identity.